Pelatihan Pemanfaatan Teknologi Media Sosial Sebagai Sarana Promosi Ukm Di Desa Bukit Lawang Kecamatan Bahorok Sumatera Utara - Adidtya Perdana; Yuyun Dwi Lestari (LPPM STIKOM Tunas Bangsa, 2020)
SMEs or Small and Medium Enterprises are business units that have an important role in the development of national economic growth, and are able to absorb labor in the processing and distribution of production results. The products of UKM are able to help the people's economy which becomes a new field of work. However, the obstacle in the business processes of these SMEs is the difficulty in getting the right consumers so that production results are not sold and cause losses. This problem is caused by the lack of good and appropriate promotion of the products of these SMEs. So we need a means or media so that these SMEs can properly promote their production results. For this reason the writer and the team carry out training activities for SMEs in the village of Bukit Lawang, Bahorok District, North Sumatra in the use of social media as a means of promoting production results. The training was held to be able to provide knowledge to SME entrepreneurs in promoting the results of their businesses appropriately to consumers through social media. Where social media is the most popular and very cheap promotional media at the moment.